Notice of a Small Urn, of the so-called ’Incense Cup’ type, found at Barnfauld, Threepwood, Parish of Beith, in the early part of the present century, and now presented to the Museum - Dobie, John Shedden (Proceedings of the Society of Antiquaries of Scotland, 1878)